Somatotype, the risk of hydroxychloroquine retinopathy, and safe daily dosing guidelines - Browning DJ (Dove Medical Press, 2018)
David J Browning, Chong Lee Department of Ophthalmology, Charlotte Eye, Ear, Nose and Throat Associates, PA, Charlotte, NC, USA Purpose: The aim of this study was to determine whether somatotype influences the risk of hydroxychloroquine (HC) retinopathy (HCR) and whether dosing by real body weight (RBW), ideal body weight (IBW), or the lesser of these better predicts the risk of HCR.Patients and methods: A total of 565 patients taking HC for whom height and weight were recorded and a sensitive ancillary testing modality was used including 10-2 visual fields, spectral domain optical coherence tomography, fundus autofluorescence imaging, and multifocal electroretinography were enrolled. Body mass index (BMI) was compared for patients without and with HCR. Logistic regression models of age, cumulative dose, and daily dosing based on RBW, IBW, or lesser of these were compared. Area under the curve (AUC) of receiver operating characteristic plots was used to assess the diagnostic accuracy of RBW, IBW, and lesser of these guidelines for safe dosing. Probability plots for the risk of retinopathy versus BMI were compared for the different recommended guidelines on safe dosing.Results: A total of 41 patients had HCR. The median BMI was 27.6 (interquartile range [IQR] 24.3, 32.6) and 24.0 (IQR 21.0, 31.6) for patients without and with HCR (P=0.0102), respectively. AUC for univariate receiver operating characteristic plots of retinopathy versus dosing by RBW, IBW, and lesser of these was 0.71, 0.72, and 0.76, respectively. AUC for multivariate receiver operating characteristic plots of retinopathy versus models incorporating gender, age, cumulative dose, and BMI and differing by including dosing by RBW, IBW, and lesser of these was 0.82, 0.82, and 0.83, respectively. For all of the multivariate logistic models, the risk of retinopathy was higher for lower BMIs.Conclusion: Short, asthenic women are at higher risk for HCR. The 2011 American Academy of Ophthalmology (AAO) guidelines are safer for short, obese women. The 2016 AAO guidelines are safer for short, asthenic patients. Choosing daily dosing based on the lesser of the RBW and IBW guidelines is safer for all patients. Keywords: hydroxychloroquine, hydroxychloroquine retinopathy, dosing guidelines, American Academy of Ophthalmology guidelines, somatotype